2016
DOI: 10.1002/ana.24599
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter prospective longitudinal study of magnetic resonance biomarkers in a large duchenne muscular dystrophy cohort

Abstract: Objective The aim of this study was to describe Duchenne muscular dystrophy (DMD) disease progression in the lower extremity muscles over 12 months using quantitative magnetic resonance (MR) biomarkers, collected across three sites in a large cohort. Methods A total of 109 ambulatory boys with DMD (8.7±2.0 years; range, 5.0–12.9) completed baseline and 1-year follow-up quantitative MR imaging (transverse relaxation time constant; MRI-T2), MR spectroscopy (fat fraction and 1H2O T2), and 6-minute walk test (6M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
155
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 38 publications
(118 reference statements)
10
155
0
1
Order By: Relevance
“…4D–E). In agreement with a recent publication [18], we found that the IDEAL-CPMG sequence detected modest increases in the thigh muscles AFF in the six and seven year-old subjects whose 6MWD improved over year (Fig. 4D).…”
Section: Resultssupporting
confidence: 93%
“…4D–E). In agreement with a recent publication [18], we found that the IDEAL-CPMG sequence detected modest increases in the thigh muscles AFF in the six and seven year-old subjects whose 6MWD improved over year (Fig. 4D).…”
Section: Resultssupporting
confidence: 93%
“…Replacement of intact muscle with significant accumulation of fibrosis can affect muscle function (25,26). GAS muscle from mdx/utrn +/-mice treated with scAAVrh.74.…”
Section: Resultsmentioning
confidence: 99%
“…Natural history studies are needed to better understand the relation between the disease progression in skeletal muscles of the upper and lower limbs and in heart of patients, which is not yet clearly understood. MRI biomarkers of muscle fat percentage are responsive to disease progression in the lower limb and forearm muscles of patients with DMD 4, 23, 24. Moreover, muscle fat percentage changes were detected in the lower limb muscles of younger patients who were functionally stable or showed improvement in the functional outcome measures over 1 year 23, 25.…”
Section: Discussionmentioning
confidence: 97%
“…MRI biomarkers of muscle fat percentage are responsive to disease progression in the lower limb and forearm muscles of patients with DMD 4, 23, 24. Moreover, muscle fat percentage changes were detected in the lower limb muscles of younger patients who were functionally stable or showed improvement in the functional outcome measures over 1 year 23, 25. Imaging fatty replacement in the myocardium may be a noncontrast method of assessing the disease state of the myocardium in individuals with DMD.…”
Section: Discussionmentioning
confidence: 99%